Characterization of the Interrenal Gland and Sexual Traits Development in cyp17a2-Deficient Zebrafish - Shi, Shengchi; Shu, Tingting; Li, Xi; Lou, Qiyong; Jin, Xia; He, Jiangyan; Yin, Zhan; Zhai, Gang (Frontiers in Endocrinology, 2022)
Unlike the Cytochrome P450, family 17, subfamily A, member 1 (Cyp17a1), which possesses both 17α-hydroxylase and 17,20-lyase activities involved in the steroidogenic pathway that produces androgens and estrogens, Cytochrome P450, family 17, subfamily A, polypeptide 2 (Cyp17a2) possesses only 17α-hydroxylase activity and is known essential for the synthesis of cortisol. Besides with expressed in testes and ovaries, where the cyp17a1 is mainly expressed, cyp17a2 is also expressed in the interrenal gland in fish. Until now, the roles of cyp17a2 in fish, especially in sexual traits development and hypothalamic-pituitary-interrenal (HPI) axis, are poorly studied. To investigate the roles of Cyp17a2 in teleosts, the cyp17a2-null zebrafish was generated and analyzed by us. The significantly decreased cortisol concentration was observed both in the cyp17a2-deficient males and females at adult stage. The interrenal gland enlargement, increased pituitary proopiomelanocortin a (pomca) expression, decreased locomotion activity and response to light-stimulated stress were observed in cyp17a2-deficient fish. Intriguingly, the cyp17a2-deficient males were fertile and with normal breeding tubercles on the pectoral fin, but females were infertile, deficient in genital papilla and with decreased gonadosomatic index (GSI). The increased progesterone (P4), 17α,20β-dihydroxy-4-pregnen-3-one (DHP) and 11-ketotestosterone (11-KT) in the cyp17a2-deficient males and females were observed. The increased concentration of testosterone (T) and estradiol (E2) was observed in cyp17a2-/- females and cyp17a2-/- males, respectively. By examining the ovaries development of cyp17a2-deficient fish at 3 months postfertilization (mpf), we observed that the oocytes were over-activated. Taken together, our findings demonstrate that Cyp17a2 is indispensable for production and physiology of cortisol, and cyp17a2-deficiency resulted in diminished cortisol but accumulated P4 and DHP, which may result in the over-activated oocytes in cyp17a2-deficient females.